Improvement of Acid-Base Materials Understanding SMAI Gumukmas Students with Simple Practicum - Haryati, Tanti; Zulfikar, Zulfikar; Indarti, Dwi (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2023)
SMAI Gumukmas is a privately-funded high school situated in Purwoasri Village, Gumukmas District, Jember, with a B accreditation status. The absence of laboratory resources challenges devising inventive, uncomplicated, and pragmatic classroom learning, such as Chemistry. Collaboration between SMAI Gumukmas and the Chemistry Department lecturers to conduct community service is a mutually beneficial initiative that fosters curriculum innovation and practicum subjects. Acid-base is a chemistry topic with material relevant to all grade levels and can be easily visualized through practical examples from everyday life. The methodology involves delivering a lecture or theoretical framework on acid-base, followed by practical work. The acid-base practical is designed to commence with comprehension of the acid-base concept, including everyday life examples, before progressing to classroom implementation. The acid-base theme learning activities and practicum at SMAI Gumukmas proceeded seamlessly and successfully. The initial class consisted of 40 students from grades 11 and 12, while the subsequent consisted of 33 grade 10 students. The students exhibited a positive response as their studies progressed with exemplifications derived from everyday life.